Sexually transmitted infections among women randomised to depot medroxyprogesterone acetate, a copper intrauterine device or a levonorgestrel implant. Issue 4 (18th November 2020) - Deese, Jennifer; Philip, Neena; Lind, Margaret; Ahmed, Khatija; Batting, Joanne; Beksinska, Mags; Edward, Vinodh A; Louw, Cheryl E; Onono, Maricianah; Palanee-Phillips, Thesla; Smit, Jennifer A; Baeten, Jared M; et al.
Abstract : Objectives: Reproductive aged women are at risk of pregnancy and sexually transmitted infections (STI). Understanding drivers of STI acquisition, including any association with widely used contraceptives, could help us to reduce STI prevalence and comorbidities. We compared the risk of STI among women randomised to three contraceptive methods. Methods: We conducted a secondary analysis to assess the risk of chlamydia and gonorrhoea in a clinical trial evaluating HIV risk among 7829 women aged 16–35 randomised to intramuscular depot medroxyprogesterone acetate (DMPA-IM), a copper intrauterine device (IUD) or a levonorgestrel (LNG) implant. We estimated chlamydia and gonorrhoea prevalences by contraceptive group and prevalence ratios (PR) using log-binomial regression. Results: At baseline, chlamydia and gonorrhoea prevalences were 18% and 5%, respectively. Final visit chlamydia prevalence did not differ significantly between DMPA-IM and copper IUD groups or between copper IUD and LNG implant groups. The DMPA-IM group had significantly lower risk of chlamydia compared with the LNG implant group (PR 0.83, 95% CI 0.72 to 0.95). Final visit gonorrhoea prevalence differed significantly only between the DMPA-IM and the copper IUD groups (PR 0.67, 95% CI 0.52 to 0.87). Conclusions: The findings suggest that chlamydia and gonorrhoea risk may vary with contraceptive method use. Further investigation is warranted to better understand the mechanisms of chlamydia and gonorrhoea susceptibility in the context of contraceptive use.